Necessidades formativas de coordenadores pedagógicos em município paulista - Siqueira, Tatiane Pereira Costa (2023)
This research arose from some of the researcher's concerns when reflecting on her role as a trainer of pedagogical coordinators who work in the municipal network of Mogi das Cruzes and on the lack of clarity of how the function of the pedagogical coordinator is constituted, what are in fact their attributions and how different types of knowledge are constructed. Among the questions, the question of this research arose: what are the pedagogical coordinators' training needs in order to act as teacher trainers in the municipal schools of Mogi das Cruzes? To answer this question, the general objective of this research was: to understand the training needs of the pedagogical coordinators who work in the municipal network of Mogi das Cruzes, from the perspective of these professionals, as teacher trainers to develop indicators focused on a training project. In light of this general objective, four specific objectives were defined: (1) Identify milestones in the coordinators' personal/professional trajectories as a contribution to their work; (2) Identify the challenges that pedagogical coordinators face in order to develop teachers’ continuing training; (3) Identify how the continuing training of trainers can subsidize pedagogical coordinators to act as teacher trainers; (4) To present, as a research product, indicators for the elaboration of a training project that meets the main training needs of pedagogical coordinators who train teachers. The theoretical framework that encompasses the consistent work of the pedagogical coordinator and the continuing training of this professional was based on authors such as: Almeida (2006; 2012; 2015; 2018), Almeida and Placco (2003; 2009), Almeida and Souza (2015), Clementi (2001), Domingues (2014), Garrido (2001), Geglio (2003), Imbernón (2006), Libâneo (2004), Marcelo Garcia (1999), Nogueira (2014), Nóvoa (2017), Orsolon (2001), Placco, Almeida and Souza (2015), Placco and Silva (2001), Placco and Souza (2006; 2018), Silva and Almeida (2020), Tardif (2014), Vieira (2003) and others. Regarding the understanding of what training needs are, it was based on Pereira and Placco (2001; 2018) and Príncepe (2010). For the purposes of profiling the research subjects, all pedagogical coordinators were invited to answer a questionnaire with questions on personal and professional development. In the second phase, six pedagogical coordinators were interviewed, three with more than three years of experience in this position and three with less than that. The research takes a qualitative approach and the analysis procedures were inspired by Franco's (2003) content analysis. The interviewed coordinators revealed milestones in their personal and professional trajectories that contributed to their performance in the role of PC, challenges they face in exercising teacher training and some impressions and expectations they have about their own continuing training. From the results, some indicators were presented for the elaboration of a training project that meets the main training needs of pedagogical coordinators who train teachers